H is for hypersexual: Sexuality in youths with ADHD - Hale, Elijah W.; Murphy, Molly O.; Thompson, Katherine P. (Frontiers in Child and Adolescent Psychiatry, 2022)
Background Recent research into the association between ADHD and hypersexuality has been extremely skewed toward male patients and contribute to stigma against individuals engaging in same sex sexual behaviors. We sought to expand research on this important relationship and to address these shortcomings. Methods Using data from the TriNetX database, we created two patient cohorts of patients 21 years or younger, separated by presence or absence of ADHD diagnosis. We analyzed disorders of sexual behavior, comorbid psychiatric illness, and medication type. Those with ADHD were subdivided into same-sex high risk sexual behavior (HRSB) and opposite-sex HRSB. The ADHD group was analyzed based on the presence or absence of any disorder of sexuality. The outcomes measured were disorders of sexual behavior, comorbid psychiatric illness, and medication type. Results In a study of 1,355,184 analyzed patient records, patients ADHD were more likely to have all measured outcomes. Orientation of HRSB did not impact for disorders of sexual behavior, but individuals with same-sex HRSB were at higher risk for comorbid psychiatric illness. Those with hypersexuality and ADHD were a higher risk for psychiatric illnesses. Conclusion Our study is the largest to date examining associations between hypersexual behaviors and ADHD. Increased awareness of this association may aid in addressing some problematic behaviors before they become detrimental to the individuals with ADHD or others within their lives.